Analisis Dalam Meningkatkan Strategi Penjualan Online Produk Styrofoam - Liennt, Michael; Sihombing, Ririsma; Mulyandi, M.Rachman (Rifa'Institute, 2023)
During this pandemic, of course, sellers are pushed to be more innovate. The existence of the COVID-19 pandemic has made people flock to market products online, this has resulted in competition between sellers, especially in the food and drinks sector. Business actors need to implement the right strategy to attract customers so they don't lose out to other business actors. Therefore, this study aims to find out how the conditions of online business actors during the COVID-19 pandemic are in order to be able to compete with other online business actors. study indicate that there are several factors that cause an increase in sales, namely an increase in market demand for dummy cakes, prices and quality that are able to compete with competitor stores and an increase in the economic wheel.